Genetic counselling legislation and practice in cancer in EU Member States - McCrary, J Matt; Van Valckenborgh, Els; Poirel, Hélène A; de Putter, Robin; van Rooij, Jeroen; Horgan, Denis; Dierks, Marie-Luise; Antonova, Olga; Brunet, Joan; Chirita-Emandi, Adela; Colas, Chrystelle; Dalmas, Miriam; et al. (European journal of public health, 2024)
Background Somatic and germline genetic alterations are significant drivers of cancer. Increasing integration of new technologies which profile these alterations requires timely, equitable and high-quality genetic counselling to facilitate accurate diagnoses and informed decision-making by patients and their families in preventive and clinical settings. This article aims to provide an overview of genetic counselling legislation and practice across European Union (EU) Member States to serve as a foundation for future European recommendations and action. Methods National legislative databases of all 27 Member States were searched using terms relevant to genetic counselling, translated as appropriate. Interviews with relevant experts from each Member State were conducted to validate legislative search results and provide detailed insights into genetic counselling practice in each country. Results Genetic counselling is included in national legislative documents of 22 of 27 Member States, with substantial variation in legal mechanisms and prescribed details (i.e. the ‘who, what, when and where’ of counselling). Practice is similarly varied. Workforce capacity (25 of 27 Member States) and genetic literacy (all Member States) were common reported barriers. Recognition and/or better integration of genetic counsellors and updated legislation and were most commonly noted as the ‘most important change’ which would improve practice. Conclusions This review highlights substantial variability in genetic counselling across EU Member States, as well as common barriers notwithstanding this variation. Future recommendations and action should focus on addressing literacy and capacity challenges through legislative, regulatory and/or strategic approaches at EU, national, regional and/or local levels.